Diabetes mellitus: Possible risk and promoting factors of cholangiocarcinoma: Association of diabetes mellitus and cholangiocarcinoma. Issue 3 (June 2015) - Saengboonmee, Charupong; Seubwai, Wunchana; Wongkham, Chaisiri; Wongkham, Sopit
Graphical abstract: The mechanism of diabetes mellitus involving carcinogenesis and cancer progression. Highlights: The highest incidence of cholangiocarcinoma (CCA) is in northeastern Thailand. Liver fluke, O. viverrini (OV), infection is a strong risk of CCA in this area. Fewer than 1% of OV-infected individuals developed CCA. The review suggests diabetes mellitus may be a co-risk factor for CCA development. Abstract: The highest incidence of Cholangiocarcinoma (CCA), a malignancy of bile duct epithelia, is in the Northeast of Thailand. The liver fluke, Opisthorchis viverrini, is the known risk factor for CCA development in this region. Approximately 1% of O. viverrini infected individuals develop CCA. There could be other factors that influence the cholangiocarcinogenesis particularly in the O. viverrini infected individuals. The global epidemiological studies of risk factors for CCA in non- O. viverrini related patients indicated diabetes mellitus (DM) as a risk factor of CCA. The molecular studies in many cancers indicated that high levels of glucose, insulin and an obese condition directly and indirectly enhanced growth of cancers. For O. viverrini associated CCA, there is limited information related to DM and CCA development. High mortality rates of CCA and DM, however, were reported in the same geographical areas of northeastern Thailand. Whether DM is a factor that enhances CCA development in O. viverrini infected individuals or promotes CCA progression are discussed in a perspective of epidemiological and molecular studies.